(untitled) (Journal of Philosophy Culture and Political Science, 2015)
In this article considered the problem of spirituality in the philosophy of the first professional Kazakh philosopher Shakarim. Shakarim appears at us as the unique phenomenon of a philosophical reflection in which theological representations, syncretism and mysticism, front lines scientific and anthropological knowledge are combined. The main subject of philosophizing of Shakarim is the person, to it spiritual searches and reflections of the thinker are reduced. The philosopher painfully looks for a way of formation of the person spiritual, this purpose is defined by it the main maintenance of a human ekzistention. Shakarim defines essence of the person, his nature and appointment in knowledge, and first of all in knowledge of truth that is the acquired quality of the person. The knowledge of truth isn’t limited to purely rational knowledge as except scientific knowledge are necessary penetration of the moral beginning, knowledge of virtue here.